Susceptibility Weighted Imaging Features of Nonketotic Hyperglycemia: Unusual Cause of Hemichorea‐Hemiballismus. Issue 2 (25th February 2014) - Atay, Musa; Yetis, Huseyin; Kurtcan, Serpil; Aralasmak, Ayse; Alkan, Alpay
ABSTRACT: Nonketotic hyperglycemia has been described as a metabolic cause of Hemiballism‐hemichorea (HB‐HC), especially in elderly patients with poorly controlled diabetes. Pathophysiology is not known yet. MRI features tend to be hyperintense in the putamen on T1‐weighted images. We present conventional MRI with diffusion weighted imaging (DWI) and susceptibility weighted imaging (SWI) features of two cases with nonketotic hyperglycemia. T1 hyperintensity without diffusion restriction on DWI and minimal putaminal hypointensity without phase shift on SWI were compatible with either pathological mineralization or petechial microhemorrhage or protein denaturation. In the type 2 diabetic patients with HC‐HB, conventional MRI together with SWI and DWI will guide to clinician to plan treatment approach.